Pengaruh Produk, Promosi Dan Proses Terhadap Keputusan Konsumen Pada Kantor BPJS Ketenagakerjaan Kota Medan - Tenang Ukur Ardianta Ginting, Samuel; Ginting, Charisma Kuriata; Nurhafidzah; Br Tarigan, Selvida Riahta (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2025)
Increased attention to workers in Indonesia through various guarantee claims such as Old Age Security, Death, Work Accidents, Pensions, and Job Loss, by prioritizing the condition of the community as part of self-protection continues to be developed by the Medan In its function as the Social Security Organizing Agency, the City Branch of BPJS Employment is responsible for providing socioeconomic protection to the community in accordance with the state's budgetary capability. This study aims to ascertain how products, promotions, and procedures affect consumer choices at the BPJS Employment Office in Medan City. Which variable is more dominating, then? The dependent variable (Y) is consumer decisions, whereas the independent variables (X) are product (X1), promotion (X2), and process (X3). By examining the magnitude of the regression coefficient, the results of the multiple correlation test (R), the results of the multiple determination coefficient test, and the results of the partial coefficient test (r), the research method, which employs quantitative descriptive analysis, concluded that each variable (X) can have an impact on the variable (Y). With the use of the SPSS software application, the quantitative approach analyzes data using statistical procedures and numbers. The output of this research is published in the Journal Online System (OJS). With this, the researcher is interested in raising the research title "The Influence of Products, Promotions and Processes on Consumer Decisions at the Medan City BPJS Employment Office".